Design Strategies for High‐Voltage Aqueous Batteries. Issue 7 (19th April 2021) - Dong, Chongrui; Xu, Fei; Chen, Long; Chen, Zhongxue; Cao, Yuliang
Abstract : Due to the intrinsically safety issues derived from the use of flammable organic liquid electrolytes, the prospect of nonaqueous metal‐ion batteries for large‐scale energy storage applications is suspended. Instead, the highly safe and environmentally friendly aqueous metal‐ion batteries have attracted considerable attention as promising candidates during the past decade. Despite significant advances in cycle life, challenges including narrow electrochemical stability window (ESW) and scalability still hinder the practical application of aqueous battery. Herein, the recent progress toward the broadening of potential window for aqueous battery, with emphasis on the design and modification of electrolyte, electrode, and current collectors are comprehensively summarized. Moreover, the commercial prospects of various alternative electrolytes are critically appraised in terms of the potential window, material sustainability, ionic conductivity, safety, and manufacturability. It is anticipated that the insights presented here can offer a guidance for future research on high‐voltage aqueous batteries. Abstract : Expanding the electrochemical stability window (ESW) is the key route for the development of high‐energy‐density aqueous rechargeable metal‐ion battery. The recent progress in the design and modification of electrolyte, electrode, and current collectors are comprehensively summarized with the aim of providing a guidance for future research toward broadening the potential window of aqueous battery.